Factors associated with negative energy balance in periparturient dairy cows raised under tropical climate of Thailand—A mini-review (Journal of Advanced Veterinary and Animal Research, 2021)
This review attempted to explain factors associated with negative energy balance (NEB) occurring during the periparturient period in dairy cows raised under tropical climatic conditions. The NEB has long been proven as an inevitable event in periparturient dairy cows. This condition had negative effects on the overall performances of dairy cows, including milk production, reproduction, and health condition. Therefore, periparturient management to overcome the NEB problem is vital for optimizing profit in dairy farming. In most tropical countries such as Thailand, dairy cows have been predominantly kept by small-holder farmers. Consequently, baseline milk yields, feed availability, feeding management, and general farming practices are different from typical commercial dairy farming. Heat stress also plays a crucial role in NEB conditions, and elevated temperature-humidity indexes above-normal conditions are recorded throughout the year. These factors influence the NEB in tropical dairy cows, which could result in different outcomes and consequences. Understanding the affecting components of NEB in dairy cows would help alleviate the severity of the NEB and its consequences, optimizing the dairy cow’s performance.J. Adv. Vet. Anim. Res., 8(3): 378-387, September 2021http://doi.org/10.5455/javar.2021.h526